1978
DOI: 10.2136/sssaj1978.03615995004200010020x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effects of Calcium Silicate in Tropical Soils: I. Fate of Applied Silicon During Five Years Cropping

Abstract: A field experiment was conducted at the Kauai Branch Station to study the long‐term effects of calcium silicate applied to a Gibbsihumox soil. The fate of applied Si was determined during 5 years of cropping at one P (280 kg/ha) and three pH levels (5.5, 6.0, and 6.5). Plant uptake by the sugarcane plant (Saccharum officinarum L.) and ratoon crops, corn, (Zea mays L.), and seven harvests of kikuyugrass (Pennesetum clandestinum H.) accounted for 12 to 21% of the applied Si. Repeated extraction of profile sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
5

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
4
13
0
5
Order By: Relevance
“…A concentração de silício foi maior com a fonte silicato de sódio (Tabela 1), devido a maior solubilidade do produto, comparado ao silicato de cálcio, favorecendo maior absorção do elemento. Com relação às doses, o teor de silício no caule reduziu até a dose de 0,53 g.kg (Khalid et al, 1978). Fontes de silicato de cálcio provenientes de siderurgia, 'Wollastonita', silicato de magnésio e termofosfato foram avaliadas por Korndörfer & Gascho, 1999, em quatro tipos de solo.…”
Section: Resultsunclassified
“…A concentração de silício foi maior com a fonte silicato de sódio (Tabela 1), devido a maior solubilidade do produto, comparado ao silicato de cálcio, favorecendo maior absorção do elemento. Com relação às doses, o teor de silício no caule reduziu até a dose de 0,53 g.kg (Khalid et al, 1978). Fontes de silicato de cálcio provenientes de siderurgia, 'Wollastonita', silicato de magnésio e termofosfato foram avaliadas por Korndörfer & Gascho, 1999, em quatro tipos de solo.…”
Section: Resultsunclassified
“…The phosphate extractant with 3.5 pH adjusted with acetic acid (HAOc) may have some advantages because it seems to extract adsorbed Si (capacity factor) as well as water-soluble Si (intensity factor) from soil. (Fox et al, 1967a;Khalid et al, 1978). Korndörfer et al (1999b) working with upland rice and four different soils concluded that among the extractants tested, the acetic acid 0.5 M gave the best estimate for the available Si in the soil.…”
Section: Soil Testingmentioning
confidence: 99%
“…Their dissolution is triggered by acidity production, and the risk of pH overshooting is prevented (31). Wollastonite (CaSiO 3 ) powder, a fast-dissolving calcium silicate, is commonly used in agronomy as a liming agent (32,33), but the utilization of silicates for remediation of contaminated water bodies and groundwater has rarely been investigated. The addition of wollastonite to an anthropogenically acidified stream was found to be highly effective in increasing the pH and the acid-neutralizing capacity of stream water (34,35).…”
mentioning
confidence: 99%